Temperature‐Induced Sign Inversion of Circularly Polarized Luminescence of Binaphthyl‐Bridged Tetrathiapyrenophanes - Takaishi, Kazuto; Yoshinami, Fumiya; Sato, Yoshihiro; Ema, Tadashi (Chemistry : a European journal, 2024)
D2‐symmetric (R)‐binaphthyl‐bridged pyrenophanes containing thioether bonds were synthesized. The pyrenophanes exhibited the temperature‐induced sign inversion of circularly polarized luminescence (CPL) while maintaining the emission wavelength and reversibility. The Δglum value reached 0.02, and the FL quenching by heat was negligible. The sign inversion of CPL originates from the inversion of intramolecular excimer chirality associated with excitation dynamics. The two pyrenes form a kinetically trapped left‐handed twist excimer at low temperatures, while they form a thermodynamically favored right‐handed twist excimer at high temperatures. The thioether linkers can impart flexibility suitable for the inversion of chirality of the excimers. D2‐symmetric (R)‐binaphthyl‐bridged pyrenophanes with thioether linkers exhibited the temperature‐induced sign inversion of circularly polarized luminescence (CPL). The peculiar excitation dynamics responsible for the inversion was revealed; the pyrenes form a kinetically trapped left‐handed twist excimer at low temperatures, while they form a thermodynamically favored right‐handed twist excimer at high temperatures.